2018
DOI: 10.1039/c8ra06886k
|View full text |Cite
|
Sign up to set email alerts
|

Tungstic acid-functionalized Fe3O4@TiO2: preparation, characterization and its application for the synthesis of pyrano[2,3-c]pyrazole derivatives as a reusable magnetic nanocatalyst

Abstract: A new magnetic nanocatalyst based on the immobilization of tungstic acid onto 3-chloropropyl-grafted TiO 2 -coated Fe 3 O 4 nanoparticles (Fe 3 O 4 @TiO 2 @(CH 2 ) 3 OWO 3 H) was prepared, characterized, and applied for the synthesis of pyrano[2,3-c]pyrazole derivatives. The characterization was performed using FT-IR spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive Xray spectroscopy (EDS), and vibrating sample magnetometry (VSM) analysis. Pyranopyrazoles were synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…FESEM study showed that the nanoparticles had a spherical morphology with size < 100 nm. The target molecules were prepared by a multicomponent reaction between malononitrile (3), 3-methyl-pyrazolone (8) and aldehydes (82) in the presence of Fe 3 O 4 @FSM-16-SO 3 H (30 mg) in a water-ethanol system in high yields (79-89%) for 80 min at reflux condition (Scheme 23). The recovered catalyst was reused five times with similar activity.…”
Section: With Bi-metallic Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…FESEM study showed that the nanoparticles had a spherical morphology with size < 100 nm. The target molecules were prepared by a multicomponent reaction between malononitrile (3), 3-methyl-pyrazolone (8) and aldehydes (82) in the presence of Fe 3 O 4 @FSM-16-SO 3 H (30 mg) in a water-ethanol system in high yields (79-89%) for 80 min at reflux condition (Scheme 23). The recovered catalyst was reused five times with similar activity.…”
Section: With Bi-metallic Catalystsmentioning
confidence: 99%
“…The recovered catalyst was reused five times with similar activity. A facile, three-component reaction of malononitrile (3), 3-methyl-pyrazolinone (8), and aromatic aldehydes (84) leading to pyranopyrazole derivatives (85) progressed well under a solvent-free condition in 120 min at 80 • C with the aid of a low catalytic amount (0.003 g) of Fe 3 O 4 @TiO 2 @(CH 2 ) 3 OWO 3 H via one-pot manner (Scheme 24) [82]. The prepared novel catalyst was assessed by several techniques, including SEM, EDS, FT-IR, P-XRD, and VSM analysis.…”
Section: With Bi-metallic Catalystsmentioning
confidence: 99%
“…In continuation of our program aimed at developing new methodologies for the preparation of green catalysts, [81][82][83][84][85][86][87][88][89][90] we have reported preparation, characterization and catalytic application of Ni II (BAPTE)(NO 3 ) 2 -Cell as a novel cellulose-based nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these benefits and as a continuation of our studies on the preparation of new heterogeneous catalysts, [34][35][36] herein we have developed synthesis and characterization of Fe 3 O 4 @TiO 2 @(CH 2 ) 3 OMoO 3 H as a novel recoverable nanocatalyst. Then, its application was investigated for the synthesis of sulfonamide containing coumarin moieties.…”
Section: Introductionmentioning
confidence: 99%